The Detection of Food Additives Using a Fluorescence Indicator Based on 6– p–Toluidinylnaphthalence-2-sulfonate and Cationic Pillar[6]arene - Duan, Qunpeng; Xing, Yibo; Guo, Kainan (Frontiers in Chemistry, 2022)
The current study investigated host-guest complexation in 6-p-toluidinylnaphthalene-2-sulfonate (TNS), a fluorescence probe used to investigate hydrophobic regions that contain the water-soluble cationic pillar[6]arene (CP6). After complexation with CP6, the fluorescence intensity of TNS was significantly increased. The decreases in the fluorescence intensity of the TNS•CP6 complex when phenolic food-additives are added have been used in indicator displacement assays to detect food additives in the water.